Original paperMyocardial regeneration strategy using Wharton’s jelly mesenchymal stem cells as an off-the-shelf ‘unlimited’ therapeutic agent: results from the Acute Myocardial Infarction First-in-Man Study - Musialek, Piotr; Mazurek, Adam; Jarocha, Danuta; Tekieli, Lukasz; Szot, Wojciech; Kostkiewicz, Magdalena; Banys, R. Pawel; Urbanczyk, Malgorzata; Kadzielski, Andrzej; Trystula, Mariusz; Kijowski, Jacek; Zmudka, Krzysztof; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction: In large-animal acute myocardial infarction (AMI) models, Wharton’s jelly (umbilical cord matrix) mesenchymal stem cells (WJMSCs) effectively promote angiogenesis and drive functional myocardial regeneration. Human data are lacking. Aim: To evaluate the feasibility and safety of a novel myocardial regeneration strategy using human WJMSCs as a unique, allogenic but immuno-privileged, off-the-shelf cellular therapeutic agent. Material and methods: The inclusion criterion was first, large (LVEF ≤ 45%, CK-MB > 100 U/l) AMI with successful infarct-related artery primary percutaneous coronary intervention reperfusion (TIMI ≥ 2). Ten consecutive patients (age 32–65 years, peak hs-troponin T 17.3 ±9.1 ng/ml and peak CK-MB 533 ±89 U/l, sustained echo LVEF reduction to 37.6 ±2.6%, cMRI LVEF 40.3 ±2.7% and infarct size 20.1 ±2.8%) were enrolled. Results: 30 × 106 WJMSCs were administered (LAD/Cx/RCA in 6/3/1) per protocol at ≈ 5–7 days using a cell delivery-dedicated, coronary-non-occlusive method. No clinical symptoms or ECG signs of myocardial ischemia occurred. There was no epicardial flow or myocardial perfusion impairment (TIMI-3 in all; cTFC 45 ±8 vs. 44 ±9, p = 0.51), and no patient showed hs-troponin T elevation (0.92 ±0.29 ≤ 24 h before vs. 0.89 ±0.28 ≤ 24 h after; decrease, p = 0.04). One subject experienced, 2 days after cell transfer, a transient temperature rise (38.9°C); this was reactive to paracetamol with no sequel. No other adverse events and no significant arrhythmias (ECG Holter) occurred. Up to 12 months there was one new, non-index territory lethal AMI but no adverse events that might be attributable to WJMSC treatment. Conclusions: This study demonstrated the feasibility and procedural safety of WJMSC use as off-the-shelf cellular therapy in human AMI and suggested further clinical safety of WJMSC cardiac transfer, providing a basis for randomized placebo -controlled endpoint-powered evaluation.